Kontrak Kerja dalam Hukum Bisnis Ketenagakerjaan: Analisis Perlindungan Hukum Hak dan Kewajiban Para Tenaga Kerja - Hanipah, Aumalia; Dalimunthe, Nikmah; Pertiwi, Sri Indah; Sitompul, Humaidi (Maliyah : Jurnal Hukum Bisnis Islam, 2023)
Many workers in Indonesia experience violations of legal protection for their rights and obligations as workers, which is based on their ignorance of what a work contract is and what rights and obligations workers have. This forms the basis of this research, with the aim of analyzing employment contracts in the field of labor law: an analysis of the legal protection of workers' rights and obligations. The data analysis in this research uses qualitative methodology with a descriptive research design. Furthermore, this study reveals that labor law will always be related to the protection of workers' rights and obligations. In the field of labor law, an employment contract is defined as a written agreement between an employee and an employer that regulates various aspects of their working relationship. This contract serves as a legal framework that protects the rights and obligations between both parties. Legal protection is an effort to safeguard the dignity and human rights of legal subjects in accordance with applicable laws and regulations, whether in the form of policies or rules that can protect something from other threats. Rights and responsibilities between parties are interrelated, where one party's rights imply obligations for the other party.